Highly Stable Pt‐Based Ternary Systems for Oxygen Reduction Reaction in Acidic Electrolytes. Issue 41 (27th September 2020) - Kim, Jun; Hong, Yongju; Lee, Kwangyeol; Kim, Jin Young
Abstract: In the era of the global rise of energy consumption and the accompanying environmental issues, energy production via fuel cells plays a vital role in a clean, secure, and affordable energy future. The development of Pt‐based binary alloy catalysts for the oxygen reduction reaction (ORR) has contributed significantly to the commercial realization of fuel cells, such as polymer electrolyte membrane fuel cells (PEMFCs) and phosphoric acid fuel cells (PAFCs). However, the short lifetime of the Pt‐based binary alloy catalyst remains a significant gap between lab‐scale and real‐device evaluation systems, calling for the development of catalysts that do not have stability issues. Among the various catalyst systems developed as alternatives to Pt‐based binary alloy catalysts, Pt‐based ternary systems with an additional element to the binary systems seem to provide the much‐awaited answer toward enhanced catalyst stability. Here, this progress report focuses on fundamental challenges of industrial fuel cell applications and provides broad and balanced insights on remarkable progress to date. Finally, it presents several perspectives on ideal ternary system design of efficient and robust Pt‐based electrocatalysts and guidance for future development beyond the academic level. Abstract : Current challenges in developing binary Pt alloy catalysts for fuel cells are addressed, emphasizing the importance of catalyst stability during fuel cell operation. In particular, a comprehensive list of studies on Pt‐based ternary electrocatalysts is detailed, primarily focused on improving catalyst stability, and the favorable effects of third metals are systematically organized based on their local distribution in nanoparticles.